Heat stable enterotoxin produced by Escherichia coli in acute diarrhoea. Issue 6 (June 1989) - Guarino, A; Alessio, M; Tarallo, L; Fontana, M; Iacono, G; Gobio Casali, L; Guandalini, S
Abstract : We screened 569 children with acute onset diarrhoea from five Italian towns for heat stable enterotoxin produced by Escherichia coli. We compared an enzyme linked immunoabsorbent assay (ELISA) with the standard suckling mouse assay for detection of the enterotoxin. A total of 31 (5.4%) children were found who had strains of E coli that produced heat stable enterotoxin: 26 strains were positive in both tests, four only in the suckling mouse assay, and one only in the ELISA. Compared with the suckling mouse assay the sensitivity of the ELISA was 87% and the specificity was 99.8%. The mean age of the children with E coli that produced heat stable enterotoxin was 22 months. Fifteen (48%) of the children had ingested potentially contaminated food and five (17%) had a previous contact with someone with diarrhoea. The clinical picture was milder than that described in developing countries. Faecal osmolality and the osmolal gap were consistent with a secretory diarrhoea in 12 out of 15 (80%) of these children. The mean duration of the diarrhoea was five days. Heat stable enterotoxin produced by E coli is a common cause of mild diarrhoeal illness in Italian children.